2019
DOI: 10.1016/j.nicl.2019.101745
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmacological and pharmacological interventions relieve insomnia symptoms by modulating a shared network: A controlled longitudinal study

Abstract: BackgroundPrimary insomnia (PI) is one of the most common complaints among the general population. Both non-pharmacological and pharmacological therapies have proven effective in treating primary insomnia. However, the underlying mechanism of treatment remains unclear, and no studies have compared the underlying mechanisms of different treatments.MethodsIn this study, we investigated gray matter volume (GMV) and resting-state functional connectivity (rsFC) changes following both pharmacological and non-pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 71 publications
(91 reference statements)
1
8
0
1
Order By: Relevance
“…These studies prove the important role of the hippocampus in the neuropathology of insomnia. Feng's study found that after cupping intervention, the PSQI score of insomnia patients decreased the hippocampus volume increased and the brain function link between the hippocampus and the anterior cingulate cortex and the medial prefrontal cortex increased signi cantly (44). Therefore, when studying ARQE, while observing the improvement of patients' insomnia symptoms, we will also observe the correlation between the improvement of patients' insomnia symptoms and the function of brain regions, especially the hippocampus and other important areas.…”
Section: Discussionmentioning
confidence: 95%
“…These studies prove the important role of the hippocampus in the neuropathology of insomnia. Feng's study found that after cupping intervention, the PSQI score of insomnia patients decreased the hippocampus volume increased and the brain function link between the hippocampus and the anterior cingulate cortex and the medial prefrontal cortex increased signi cantly (44). Therefore, when studying ARQE, while observing the improvement of patients' insomnia symptoms, we will also observe the correlation between the improvement of patients' insomnia symptoms and the function of brain regions, especially the hippocampus and other important areas.…”
Section: Discussionmentioning
confidence: 95%
“…Researchers found a reduction in the symptoms of insomnia in groups treated with cupping therapy and benzodiazepines [31]. Thus, DC proved to be a promising therapeutic resource for sleep disorders, and even better results are expected when associated with EA.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies have shown that the PFC is involved in sleep processes. For example, after 4 weeks of pharmacologic intervention in patients with PI, Feng et al 37 found that PSQI scores were decreased, and this was significantly associated with increased FC between the mPFC and hippocampus. Park et al 38 reported that improved sleep quality after cognitive behavioral therapy was correlated with increased FC between the PFC and DMN.…”
Section: Discussionmentioning
confidence: 99%